Extremal Copulas and Tail Dependence in Modeling Stochastic Financial Risk - Mallam, Hassane Abba; Moutari, Natatou Dodo; Diakarya, Barro (European Journal of Pure and Applied Science, 2021)
These last years the stochastic modeling became essential in financial risk management related to the ownership and valuation of financial products such as assets, options and bonds. This paper presents a contribution to the modeling of stochastic risks in finance by using both extensions of tail dependence coefficients and extremal dependance structures based on copulas. In particular, we show that when the stochastic behavior of a set of risks can be modeled by a multivariate extremal process a corresponding form of the underlying copula describing their dependence is determined. Moreover a new tail dependence measure is proposed and properties of this measure are established.
European Journal of Pure and Applied Mathematics, 14(3), 1057–1081.
Keywords: Copulas; extreme values theory; stochastic process; Value at risk; Tail dependence; CEFORGRIS; Joseph Ki-Zerbo University and Ouaga II University; Burkina Faso